2018
DOI: 10.1371/journal.pone.0205789
|View full text |Cite
|
Sign up to set email alerts
|

Variability in pharmacologically-induced coma for treatment of refractory status epilepticus

Abstract: ObjectiveTo characterize the amount of EEG suppression achieved in refractory status epilepticus (RSE) patients treated with pharmacologically-induced coma (PIC).MethodsWe analyzed EEG recordings from 35 RSE patients between 21–84 years-old who received PIC that target burst suppression and quantified the amount of EEG suppression using the burst suppression probability (BSP). Then we measured the variability of BSPs with respect to a reference level of BSP 0.8 ± 0.15. Finally, we also measured the variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Some reports have not found an association between specific comainducing agents or the extent of BS on outcome [3], while others have raised concerns about the higher morbidity and mortality in BS group, mostly due to prolonged ITU stay and anaesthetic exposure [29]. The amount of BS achieved in clinical practice is also variable, partly due to inter-and intra-individual pharmacokinetic/pharmacodynamic variability [17], making it even more challenging to address the above issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports have not found an association between specific comainducing agents or the extent of BS on outcome [3], while others have raised concerns about the higher morbidity and mortality in BS group, mostly due to prolonged ITU stay and anaesthetic exposure [29]. The amount of BS achieved in clinical practice is also variable, partly due to inter-and intra-individual pharmacokinetic/pharmacodynamic variability [17], making it even more challenging to address the above issues.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IVAT for the treatment of the pathological EEG features during RSE is far from standardised and relies mostly on pragmatic approaches [15] and weak recommendations supported by low quality evidence [1]. The endpoint against which an IVAT should be titrated [16,17] and the management of inter-ictal patterns remain controversial [18,19], yet it highlights the necessity for advanced monitoring in the form of continuous critical care EEG (cCCEEG) [20,21] to avoid IVAT-related sideeffects [22].…”
Section: Introductionmentioning
confidence: 99%
“…A study evaluated the variability of the BS pattern in 35 RSE patients in TC, with the reference BS ratio being 0.8 + 0.15. 21 Only 8% (median, IQR 0%-29%) of total time was spent at the reference BS range. This study highlighted the remarkable variability of the amount of BS within patients.…”
Section: Commentarymentioning
confidence: 98%
“…Clinical trials are needed to determine how efficacious this treatment is (Rossetti and Lowenstein, 2011). Other recent studies have indicated that burst suppression is inconsistently maintained during such treatment (An et al, 2018).…”
Section: Controversy Regarding Use Of Burst Suppression As a Neuroprotective Toolmentioning
confidence: 99%